Analysis of respiratory pathogens in pediatric acute respiratory infections in Lanzhou, Northwest China, 2019-2024 - Wang, Qian; Pan, Yunyan; Gao, Hongwei; Zhao, Youli; Gao, Xinzhe; Da, Yichen; Niu, Shaomin; You, Chongge (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to assess the prevalence and distribution of respiratory pathogens in children under 18 years old with Acute Respiratory Infections (ARTIs) in Lanzhou, Northwest China, from July 2019 to January 2024.MethodsThe respiratory pathogens studied were FluA, FluB, PIV, RSV, ADV, MP, CP, CB, and LP, detected by indirect immunofluorescence assay (IIF). Data were obtained from the laboratory information system (LIS) of the Lanzhou University Second Hospital. As in Lanzhou, NPIs were implemented in January 2020, and were lifted in December 2022, data were divided into pre-NPIs (July 2019 to December 2019), NPIs (January 2020 to December 2022) and post-NPIs (January 2023 to January 2024) periods for analysis. Pearson’s chi-square test, ANOVA, and Fisher’s exact test were used to evaluate statistical significance in variable differences, with P < 0.05 considered significant.ResultsA total of 29,659 children diagnosed with ARTIs were included in the study, with 13030(43.93%) test positive for at least one pathogen. Single-pathogen infections predominated (33.10%), while co-detection of MP and PIV was the most common among multi-pathogen cases (52.96%). Pathogen detection rates were notably higher in female children (50.62%) and preschool-aged children (53.45%) and exhibited seasonal variations, with a pronounced increase in winter (47.61%) and a peak in November (48.92%). MP had the highest detection rate (38.59%), followed by PIV (10.18%). Detection rates significantly increased following the lifting of NPIs, rising from 33.82% (SD ± 13.13) during NPIs to 64.42% (SD ± 4.67) (P < 0.001), with 2023 showing the highest detection rate (64.61%) and largest participant count (9,591). In November 2023, detection rates reached their highest level at 73.09%. Post-NPI, most pathogens, except CB and LP, demonstrated significantly higher prevalence (P<0.001).ConclusionIn the Lanzhou region, MP and PIV were identified as the most prevalent respiratory pathogens among children with ARTIs, with peak detection rates during the winter season. Boys and school-age children exhibited higher susceptibility to these infections. NPIs played a critical role in reducing respiratory pathogen transmission. Once NPIs were lifted, a marked resurgence in pathogen incidence highlighted their impact on controlling infection spread.